El reflejo epigráfico de las tristes vicisitudes personales de un procurator Augusti: Sextus Truttedius Clemens - Mayer, Marc (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
The career of Sextus Truttedius Clemens provides us not only with important prosopographical data on provincial procurators, but also with an exceptional number of personal details about the private life of this procurator, which we have studied in detail here. We also present an alternative reading for an inscription from Fanum Fortunae, Fano, which may alter the interpretation found in scholarly literature. Furthermore, we assert that all the epigraphic references, and particularly one from Ancona, refer to procurator under study.